Ultrastructure and pollen morphology of Bromeliaceae species from the Atlantic Rainforest in Southeastern Brazil - Silva,Vanessa J.D. (2016)
Pollen grain morphology of Bromeliaceae species collected in areas of the Atlantic Rainforest of southeastern Brazil was studied. The following species were analyzed: Aechmea bambusoides L.B.Sm. & Reitz, A. nudicaulis (L.) Griseb., A. ramosa Mart. ex Schult.f., Ananas bracteatus (Lindl.) Schult.f., Billbergia distachia (Vell.) Mez, B. euphemiae E. Morren, B. horrida Regel, B. zebrina (Herb.) Lindl., Portea petropolitana (Wawra) Mez, Pitcairnia flammea Lindl., Quesnelia indecora Mez, Tillandsia polystachia (L.) L., T. stricta Sol., T. gardneri Lindl., T. geminiflora Brongn. and Vriesea grandiflora Leme. Light and scanning electron microscopy were used and the species were grouped into three pollen types, organized according to aperture characteristics: Type I - pantoporate pollen grains observed in P. petropolitana, Type II - 2-porate pollen grains, observed in the genera Ananas, Aechmea and Quesnelia, and Type III - 1-colpate pollen grains, observed in the genera Billbergia, Pitcairnia, Tillandsia and Vriesea. Pollen data led to the construction of an identification key. The results showed that the species analyzed can be distinguished using mainly aperture features and exine ornamentation, and that these characteristics may assist in taxonomic studies of the family.